Van vroegchristelijk tot seculier universalisme en tolerantie bij Slavoj Žižek en Stefan Hertmans - Srebnik, Anita (Slavia Centralis, 2020)
The early Christian universalism became all but universal with the arrival of the apostle Paulus. The universalism excluded the Other and since Paulus there is a strong tendency towards homogenisation and egalisation which is present in Christianity up to this day and is noticeable throughout our social system. Consequently, the intolerance toward the Other is a frequent occurrence and the way out is not just being tolerant toward the Other and keeping the appropriate distance. At the same time one should attempt an emancipatory struggle, which is deeply rooted already in the early Christian teachings, i.e. rise above the particular identity – to be able to find the universality of humanity.